Seven Years in the Field of Health Impact Assessment: Taking Stock and Future Directions - Rebecca Morley, MSPP; Ruth Lindberg, MPH, MUP; Bethany Rogerson, MSSP; Emily Bever; Keshia M. Pollack, PhD, MPH (Indiana University-Purdue University Indianapolis, 2016)
The U.S. spends more per person on medical care than any other country, yet we have worse health indicators than many comparable wealthy nations. Research increasingly shows that social, economic, and environmental factors determine our health; however, there is still an emphasis on curing illnesses rather than addressing these underlying causes of disease. The Health Impact Project is a collaboration of the Robert Wood Johnson Foundation and The Pew Charitable Trusts, established in 2009 to promote and support the use of health impact assessment (HIA). As of January 2016, there were 386 HIAs either completed or in progress in the US in a variety of sectors-up from 62 HIAs in 2009. Although built environment HIAs still make up the largest sector of practice, other topics are emerging including education, criminal justice, and labor and employment. As the field matures, we are presented with new opportunities and challenges. In this article we offer lessons learned from our experience over the last seven years, and a view into the future of HIA. Specifically, we discuss the challenges and promises of making health a routine consideration in decision-making, translating HIA recommendations into policy, monitoring and evaluating the impact and outcomes associated with HIAs, promoting health considerations in federal decisions, and using HIAs as a tool for promoting health equity.